LLM-SEMREL: Towards a Better Coreference Resolution for Portuguese - Fonseca, Evandro; Neto, Joaquim (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2024: Anais do XV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2024)
This paper aims to describe LLM-SEMREL, a new Portuguese semantic database built automatically using currently available large language models. The motivation for this project stems from the lack of rich semantic resources for the Coreference Resolution task in Portuguese. As a result, we provide a new resource that can be used to improve current models and build new ones. LLM-SEMREL is composed of 1,229,399 semantic relations, distributed among 261,731 words and their descriptions.